Impact of patients' age and comorbidities on prostate cancer overdiagnosis in clinical practice. - Abraham Beltrán; Lucy Parker; Irene Moral-Pérez; Juan Pablo Caballero-Romeu; Elisa Chilet-Rosell; Ildefonso Hernández-Aguado; Pablo Alonso-Coello; Elena Ronda; Luis Gómez-Pérez; Blanca Lumbreras (PLoS ONE)
Introduction Overdiagnosis in PSA-based prostate cancer (PCa) screening is primarily studied in younger, healthier populations from clinical trials. This study aimed to evaluate the probability of overdiagnosis in PCa screening within a clinical practice context, focusing on its relationship with PSA levels, Gleason scores, and subsequent clinical procedures. Methods We conducted a retrospective cohort analysis of 1,070 asymptomatic men over 40 years old diagnosed with PCa between 2004 and 2022, following a positive PSA test. The patients were followed until December 31, 2022, with a median follow-up time of 5.7 years (IQR 3.2-8.6). The primary outcome was the probability of overdiagnosis, assessed through life expectancy and the Charlson Comorbidity Index, considering lead times of 5, 10, and 15 years. Results We found that patients with PSA levels >10 ng/dL and/or Gleason scores ≥8 were generally older and had more comorbidities than those with PSA levels 4-10 ng/dL and/or Gleason scores ≤7. The probability of overdiagnosis was significantly higher in patients with PSA levels >10 ng/dL (41.4%, IQR 21.5-73.9) and Gleason scores ≥8 (42.6%, IQR 14.9-38.9), compared to those with PSA levels 4-10 ng/dL (20.1%, IQR 12.8-30.4) and Gleason scores ≤7 (26.6%, IQR 23.6-68.6). Notably, 71.7% of patients did not receive pharmacological treatment. Patients with higher PSA levels also experienced greater radiation exposure from diagnostic imaging (median 19.9 mSv vs. 14.7 mSv, p = 0.004). Conclusions These findings underscore the high likelihood of overdiagnosis in older patients with elevated PSA levels and significant comorbidities, highlighting the need for careful consideration of patient comorbidities before PSA testing.